Prospective analysis of factors associated with dental behavior management problems, in children aged 7-11 years - Ramya Pai; Praveenkumar Mandroli; Deepa Benni; Pallavi Pujar (Wolters Kluwer Medknow Publications, 2015)
Aim: To determine the prevalence of child behavior management problems (BMP) and to analyze the influence and predictive power of nondental and dental background variables on BMP. Study Design: Prospective analytical study. Materials and Methods: The study group included 165 children aged 7-11 years who received comprehensive dental treatment, after obtaining written informed consent. Parents/guardians were interviewed using standardized questionnaire to obtain background information. Each child's treatment was carried out and was recorded with a fixed digital video (DV) recorder. The treatments were classified into three levels of invasiveness: Noninvasive (NI), moderately invasive (MI), and highly invasive (HI). The entire DV record of each treatment was observed, and child's dental behavior was rated independently by two precalibrated examiners using modified Venham's behavior rating scale. Then, the background factors obtained through the questionnaire data were analyzed for its association with child's dental behavior. Results: Statistical tests used were Chi-square test and multiple logistic regression analysis to determine the relationship of multiple variables with dental behavior. Comparison of child's behavior during different visits was done by Wilcoxan matched pairs test. The prevalence of BMP in children aged 7-11 years in the study sample was 0%, 4.2%, and 15.76% for NI, MI, and HI procedures, respectively. Three variables were significant predictors of behavior; order of birth that is, first born, history of hospitalization, and unpleasant past dental experience (P < 0.05). Conclusions: Direct conditioning pathway is the major factor in determining child's behavior. Dental experiences, duration of treatment, and complexity of treatment have greater impact on how the child behaves in a dental setup.